UNIVERSITY IN THE CONTEXT OF REGIONAL TASKS - Nikolay Denisovich Tskhadaya (Высшее образование в России)
The article reveals the role of Ukhta State Technical University in economic development and sociocultural life of Komi Republic. The article presents the main stages of the university’s activities during the last ten years and its key tasks for promoting social and economic development of the region. The first task is formation of the university complex, and diversification of the range of educational services. The second concerns therealization of the idea of continuing education in accordance with a formula “Ukhta is a university city”. The third taskis closely connected withthe problem of monocities and therole ofthe university in its solving. The fourth is the accomplishment of auniversity project “Ukhta is the fatherland of the first Russian petroleum”.